1988
DOI: 10.1016/s0022-5347(17)42618-8
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Model AMS 700 Penile Prosthesis: Long-Term Results

Abstract: The American Medical Systems inflatable penile prosthesis has undergone periodic design changes to improve device reliability and longevity while maintaining a high degree of patient and partner satisfaction. Previous data reported from this institution did not consider these frequent design changes and the assessment of device reliability incorporated consecutive cases involving several different designs. This study was designed to evaluate followup data on 120 patients who received the model 700 inflatable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…As far as infectious complications are concerned, we also report slightly higher results than those in the litera ture [3,10,12,14,19,[21][22][23][24][25][26][27][28] (table 6). Noticeable is the fact that the 3 early infections were easily diagnosed, whereas the 5 others were diagnosed intraoperatively after surgical exploration for chronic painful penile syn dromes which evolved over several months.…”
Section: Methodsmentioning
confidence: 50%
See 1 more Smart Citation
“…As far as infectious complications are concerned, we also report slightly higher results than those in the litera ture [3,10,12,14,19,[21][22][23][24][25][26][27][28] (table 6). Noticeable is the fact that the 3 early infections were easily diagnosed, whereas the 5 others were diagnosed intraoperatively after surgical exploration for chronic painful penile syn dromes which evolved over several months.…”
Section: Methodsmentioning
confidence: 50%
“…However, the initial enthusiasm for this type of treatment has been moderated by the onset of mainly mechanical and infectious complications [8][9][10][11][12][13][14][15][16], Only 45% of our patients had a perfect mechanical result (table 2). This result is inferior to those reported in the literature [16][17][18] for the Mentor [9,19,20] and AMS [10] prostheses. It is important, however, to notice that, unlike numerous authors for whom dysfunction is a com plication requiring surgical revision, even minor func tioning anomalies such as incomplete deflation of the device were considered a dysfunction in our series.…”
Section: Methodsmentioning
confidence: 99%
“…Furlow et al [13] conducted long-term studies on the implantation of model AMS700 penile prosthesis. Wilson et al [58] reported on 11 years experience with the inflatable penile prosthesis (Table 7).…”
Section: Prosthesis (Figures 3 4)mentioning
confidence: 99%
“…In patients who have primary placement of penile prosthesis, the re-operation rate for mechanical failure is around 5% over 5-10 years. 40,41 …”
Section: Mechanical Complicationsmentioning
confidence: 99%